2019
DOI: 10.5658/wood.2019.47.5.579
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Synthesis Method and Melamine Content of Melamine-Urea-Formaldehyde Resins on Bond-Line Features in Plywood

Abstract: This work examined effects of the synthesis method and melamine content of melamine-urea-formaldehyde (MUF) resins on the bond-line features (i.e. resin penetration and bond-line thickness) in plywood. Two synthesis methods (MUF-A and MUF-B) and three melamine contents (5, 10, and 20%) were employed to prepare MUF resins. The MUF-A resins at three melamine contents were prepared by a simultaneous reaction of melamine, urea, and formaldehyde, while the MFU-B resins were prepared by reacting melamine at the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 21 publications
3
6
0
Order By: Relevance
“…After the addition of citric acid, pMDI, and wheat flour to MF-0, the solids content of MF-1 decreased. This outcome aligns with a previous study, which reported a decrease in the solids content of melamine-based adhesives when mixed with NH 4 Cl as a hardener [ 32 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…After the addition of citric acid, pMDI, and wheat flour to MF-0, the solids content of MF-1 decreased. This outcome aligns with a previous study, which reported a decrease in the solids content of melamine-based adhesives when mixed with NH 4 Cl as a hardener [ 32 ].…”
Section: Resultssupporting
confidence: 92%
“…This content represents the total solids that contribute to the adhesive coverage on the bonded products. According to a previously published study [ 32 ], the nonvolatile solids content of melamine-based adhesives increases with a higher concentration of melamine. The inclusion of citric acid, pMDI, and wheat flour in the melamine resin mix led to a balance in the physical and chemical properties of the adhesive, resulting in a reduction of the solids content of the resin.…”
Section: Resultsmentioning
confidence: 99%
“…This trend was clearly affected by resin's viscosity and molecular weight, which also increased as a function of initial F/U mole ratio (Tables 2 and 3). This result is in agreement with the previous work that reported the relationship between bond-line thickness and resin penetration (Jeong et al, 2019;Jeong and Park, 2019b;Lubis et al, 2019) The result also showed that an in-…”
Section: Performance Of Plywood Bonded With Uf Resinssupporting
confidence: 93%
“…Statistical analysis suggested that a combination of PVOH–hexamine with 20% lignin adhesive and cold pressing for 24 h could produce plywood with comparable TSS value to the control PU resins. Several studies reported that plywood bonded with UF or melamine–urea–formaldehyde resins using hot pressing for 4–10 min had TSS values ranging from 1.0 to 1.4 MPa [ 7 , 12 , 66 , 67 , 68 , 69 , 70 ]. Markedly, a chemical modification of lignin is needed to increase its reactivity, aimed at shortening the cold-pressing time, improving the bonding strength of plywood, and increasing the production capacities for manufacturing plywood panels by cold pressing.…”
Section: Resultsmentioning
confidence: 99%